Health care professionals' perceptions of the arthroplasty patient experience: Planning phase in the development of a patient-reported outcome measure - Strickland, L; Kelly, L; Hamilton, T; Murray, D; Pandit, H; Jenkinson, C (Elsevier, 2018)
Purpose The aim of this study was to explore health care professionals’ perceptions and perspectives of surgery and early recovery for patients undergoing lower limb arthroplasty. Design Thematic analysis with semi-structured qualitative interviews. Methods Following ethical approval, interviews were performed with recovery room nurses (n=3), ward nurses (n=2), surgeons (n=5), anesthesiologists (n=5), physiotherapists (n=5), and occupational therapists (n=2). Data were analyzed using an in-depth narrative thematic analysis method. NVivo qualitative data analysis software was used. Findings Three main themes evolved from the interviews: immediate patient recovery issues, discharge criteria, and priorities during hospitalization from health care providers’ perspectives. Conclusions The early postoperative recovery period can be a challenging time for health care providers and patients alike. However, identifying key areas of importance can provide insight and guide focus in clinical practice, thus improving patient recovery.